2018
DOI: 10.1007/s13272-018-0288-1
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of slot variations on the efficiency of tangential blowing at a vertical tailplane with infinite span

Abstract: On a swept vertical tailplane with infinite span tangential blowing over the shoulder of a deflected rudder is applied. For large rudder deflection angles the flow on the rudder is separated without blowing. A numerical study is conducted with the aim to increase the side force coefficient. This could for example be required during takeoff if the engine on one side fails, necessitating the compensation of a large yawing moment. If this criterion is critical for the sizing of the vertical tailplane, active flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The slot height is 0.0006 of the local chord length leading to a relatively thin channel. This height was also used for the preceding investigations with an infinite swept wing [9]. For a middle VTP section this would be a slot height of 0.32mm.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The slot height is 0.0006 of the local chord length leading to a relatively thin channel. This height was also used for the preceding investigations with an infinite swept wing [9]. For a middle VTP section this would be a slot height of 0.32mm.…”
Section: Figmentioning
confidence: 99%
“…Therefore the full span slot is divided into several discrete slots with finite width and some gaps without slots between them. The slot width and gap size was taken from a previous investigation of an infinite swept wing with a constant chord [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, on top of transition delay and drag reduction, these methods have been proven to be effective to prevent flow separation and augment lift. A wide range of active flow control studies can be found on the subjects of flow mechanism [10,11], comparison of effectiveness of different actuators [12,13], parameter studies including geometry parameters [14], injection or suction parameters [15][16][17] and excitation parameters [18], influence of locations and layouts [19]. Some significant breakthroughs have been achieved using fluidic actuators for improving aerodynamic performance.…”
mentioning
confidence: 99%